PELATIHAN PENGEMBANGAN KERAMIK BERBAHAN BAKU TANAH LIAT OLAHAN LUMPUR LAPINDO DAN ABU GUNUNG MERAPI BAGI GURU-GURU MGMP PENDIDIKAN SENI SMP DI KABUPATEN SLEMAN YOGYAKARTA - Kasiyan, Kasiyan (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
This particular training is a program concerning: 1) developing a new clay material made of Lapindo Sidoarjo mud and ash taken from Merapi mountain Yogyakarta, and 2) to produce prototypes of ceramic products from this particular clay. The participants of this program are teachers majoring in arts and culture of junior high schools in Sleman Yogyakarta, who are the members of the art education teacher association known as Teachers Association. The program involved 25 teachers and it was conducted on June 9-13th, 2016. The main materials given in the training were related to the substance of the clay and the method of producing ceramic products using that particular clay. The program was held at Centre of Teachers' and Academic Professionals' Development and Empowerment of Art and culture Yogyakarta. The training was conducted through lecturing, discussion and demonstration and giving a practical workshop. The results of the training are as the following. First, all of the participants showed their enthusiasm and high motivation during the training. Secondly, the participants of the training were successful in making good quality ceramic products using the clay made of Sidoarjo mud and Merapi ash.